Overactivity in chronic pain: is it a valid construct?. Issue 10 (October 2015) - Andrews, Nicole Emma; Strong, Jenny; Meredith, Pamela Joy
Abstract : Abstract: Overactivity is a frequently used term in chronic pain literature. It refers to the phenomenon whereby individuals engage in activity in a way that significantly exacerbates pain, resulting in periods of incapacity. Overactivity, as a construct, has been derived solely from patients' self-reports, raising concerns about the legitimacy of the construct. Self-reported overactivity reflects an individual's "belief, " collected retrospectively, that their earlier activity levels have resulted in increased levels of pain. This may be different to an individual actually engaging in activity in a way that significantly exacerbates pain. In this study, a 5-day observational study design was used to investigate the validity of overactivity as a construct by examining the relationship between a self-report measure of overactivity, patterns of pain, and objectively measured physical activity over time. A sample of 68 adults with chronic pain completed a questionnaire investigating self-reported habitual engagement in overactivity and activity avoidance behaviour, before commencing 5 days of data collection. Over the 5-day period, participants wore an activity monitor and recorded their pain intensity 6 times a day using a handheld computer. Associations were found between (1) high levels of pain and both high overactivity and high avoidance, (2) high levels of overactivity and more variation in pain and objective activity across days, and (3) high levels of overactivity and the reoccurrence of prolonged activity engagement followed by significant pain increases observed in data sets. These results offer some preliminary support for the validity of overactivity as a legitimate construct in chronic pain. Abstract : Findings from a 5-day observation study link high levels of self-reported overactivity to repeated periods of prolonged activity engagement followed by significant pain increases.